2019
DOI: 10.1002/jbio.201800378
|View full text |Cite
|
Sign up to set email alerts
|

Widefield fluorescence lifetime imaging of protoporphyrin IX for fluorescence‐guided neurosurgery: An ex vivo feasibility study

Abstract: Achieving a maximal safe extent of resection during brain tumor surgery is the goal for improved patient prognosis. Fluorescence‐guided neurosurgery using 5‐aminolevulinic acid (5‐ALA) induced protoporphyrin IX has thereby become a valuable tool enabling a high frequency of complete resections and a prolonged progression‐free survival in glioblastoma patients. We present a widefield fluorescence lifetime imaging device with 250 mm working distance, working under similar conditions such as surgical microscopes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 24 publications
3
41
0
Order By: Relevance
“…For PpIX, a custom-made reference sample embedded in polymethylmethacrylate (Starna Scientific Ltd., Ilford, United Kingdom) was measured. 8 The measured lifetimes agreed within the range of error margins with reported literature values for the dyes in the respective solvent ( Table 1). The strongest measured lifetime deviation respective to literature (0.2 ns) was measured for fluorescein, which could be caused by the pH dependence of fluorescein lifetime.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…For PpIX, a custom-made reference sample embedded in polymethylmethacrylate (Starna Scientific Ltd., Ilford, United Kingdom) was measured. 8 The measured lifetimes agreed within the range of error margins with reported literature values for the dyes in the respective solvent ( Table 1). The strongest measured lifetime deviation respective to literature (0.2 ns) was measured for fluorescein, which could be caused by the pH dependence of fluorescein lifetime.…”
Section: Resultssupporting
confidence: 87%
“…A detailed study design can be found in our previous publication. 8 Tissue samples were imaged within an hour after resection and kept moist using artificial cerebrospinal fluid. For the first patient, the surgeon did not report any visible PpIX fluorescence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolites, such as Flavin adenine dinucleotide (FAD) or Nicotinamide adenine dinucleotide (NADH and the redox partner NAD+) have been proven valuable endogenous molecular probes of cell metabolism. Recent developments in fluorescence lifetime imaging (FLIM) show significant changes of FAD and NADH lifetime in tumour versus healthy tissue [207,208]. Fluorophores are excited in the short visible wavelength range where scattering limits large penetration depths.…”
Section: Multi-modality Imagingmentioning
confidence: 99%
“…Recently, our group developed a frequency domain FLIM system [21] around a dual-tap complementary metal-oxide semiconductor (CMOS) camera [22,23] with similar working distance and field of view (FOV) as found in modern surgical microscopes. To reconstruct the fluorescence lifetime, the camera generates several images with a phase-shifted excitation for each frame to cover a full circle of 360 degrees.…”
Section: Introductionmentioning
confidence: 99%